Nitrogen source and pH interact and modulate lipase secretion in a non-clinical strain of Candida parapsilosis (Acta Scientiarum. Biological Sciences, 2019)
Lipases (E.C. 3.1.1.3) are serine-hydrolases, and act on long chain fatty acid ester bonds. They exhibit specific and enantioselective activities, which are desirable for many industrial applications. This study aimed at screening and optimizing the production of lipases by wild yeast strains from a variety of substrates, as well as characterizing the enzyme. An initial selection was made in oxygenated oil-supplemented minimum medium, and the enzymatic activity of the supernatant was tested over p- nitrophenyl palmitate. One-hundred and twenty-four yeast strains from different substrates were tested, and twenty-three showed significantly higher lipolytic activity (p